1936
DOI: 10.1084/jem.63.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Active Immunization Against Experimental Poliomyelitis

Abstract: The results obtained in this investigation indicate that poliomyelitis virus treated with tannin, sodium ricinoleate, or formalin does not constitute a satisfactory immunizing agent in monkeys against the experimental disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1936
1936
1952
1952

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Of particular interest was the observation that convalescent monkeys were resistant to reinfection before antiviral bodies were demonstrable in their serum, and that the sera of all the monkeys tested several times 4 to 5 weeks after paralysis contained no demonstrable antibody; all monkeys, however, finally developed antibodies--some of them at 2 months and others not until 3 months after the onset of paralysis. It should be pointed out that by the use of the same test, vaccinated monkeys have been shown to contain readily demonstrable serum antibody at 5 to 6 weeks after the first inoculation without, however, exhibiting any resistance to the same amount of virus instilled intranasaUy (2). Itwasfurthermore demonstrated that the serum of convalescent monkeys, when antibody finally appeared in it, was no more potent than that of the susceptible, vaccinated monkeys.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of particular interest was the observation that convalescent monkeys were resistant to reinfection before antiviral bodies were demonstrable in their serum, and that the sera of all the monkeys tested several times 4 to 5 weeks after paralysis contained no demonstrable antibody; all monkeys, however, finally developed antibodies--some of them at 2 months and others not until 3 months after the onset of paralysis. It should be pointed out that by the use of the same test, vaccinated monkeys have been shown to contain readily demonstrable serum antibody at 5 to 6 weeks after the first inoculation without, however, exhibiting any resistance to the same amount of virus instilled intranasaUy (2). Itwasfurthermore demonstrated that the serum of convalescent monkeys, when antibody finally appeared in it, was no more potent than that of the susceptible, vaccinated monkeys.…”
Section: Discussionmentioning
confidence: 96%
“…By the use of the same test, antiviral bodies were readily detected in the serum of vaccinated monkeys which proved to be fully susceptible to the nasal instillation of poliomyelitis virus (2). It is clear, therefore, that the difference in resistance between convalescent and vaccinated monkeys is not directly related to the content of antiviral bodies.…”
Section: Correlation Between Antibody and Susceptibility To Reinfectimentioning
confidence: 96%
“…Other investigators reported an antibody response to the vaccine in monkeys, consistently (128,139) or irregularly (140). The only neutralization tests reported by others on human subjects receiving this vaccine are inconclusive (146).…”
Section: A Methodsmentioning
confidence: 99%
“…Certain experimental and clinical observations, however, do not support this view. It has been shown (27,28) that sera of monkeys injected subcutaneously with a subinfective dose of virus may after a few weeks neutralize poliomyelitis virus in vitro, even though the animals are not able to resist an intracerebral or intranasal instillation of potent virus. Further, convalescent monkeys which are refractory to reinoculation may show no neutralizing substance in their sera (29,30,31).…”
Section: Dikcussionmentioning
confidence: 99%